2012
DOI: 10.1016/s0140-6736(12)60398-5
|View full text |Cite
|
Sign up to set email alerts
|

Dabrafenib in patients with melanoma, untreated brain metastases, and other solid tumours: a phase 1 dose-escalation trial

Abstract: Background Dabrafenib (GSK2118436) is a potent ATP-competitive inhibitor of BRAF kinase and was highly selective for mutant BRAF in kinase panel screening, cell lines, and xenografts. Methods A Phase I trial of dabrafenib was conducted to evaluate safety and tolerability in patients with incurable solid tumours. Efficacy at the recommended Phase II dose (RP2D) was studied in patients with BRAF-mutant tumours, including those with non-V600E mutations, in three cohorts: (1) metastatic melanoma, (2) melanoma wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
662
0
9

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 855 publications
(703 citation statements)
references
References 33 publications
23
662
0
9
Order By: Relevance
“…42 In contrast, other mutations predict resistance to therapy; for example, detection of codon 12 mutations in KRAS predicts resistance to treatment with EGFR tyrosine kinase inhibitors in lung cancer 43 and resistance to treatment with anti-EGFR monoclonal antibodies in colorectal cancer. 44 Unexpected findings, such as the discovery of BRAF V600E in an ovarian cancer, with subsequent response to treatment with a BRAF inhibitor, 45 support the utility of sequencing genes that are not strictly characteristic for the patient's tumor type. Thus, the WUCaMP assay that we have validated here provides actionable information to direct patient care in routine practice.…”
Section: Discussionmentioning
confidence: 99%
“…42 In contrast, other mutations predict resistance to therapy; for example, detection of codon 12 mutations in KRAS predicts resistance to treatment with EGFR tyrosine kinase inhibitors in lung cancer 43 and resistance to treatment with anti-EGFR monoclonal antibodies in colorectal cancer. 44 Unexpected findings, such as the discovery of BRAF V600E in an ovarian cancer, with subsequent response to treatment with a BRAF inhibitor, 45 support the utility of sequencing genes that are not strictly characteristic for the patient's tumor type. Thus, the WUCaMP assay that we have validated here provides actionable information to direct patient care in routine practice.…”
Section: Discussionmentioning
confidence: 99%
“…Incidentally, pyrexia has been reported as a common AE with BRAF‐inhibitor monotherapy in the range of 16–26% when given as monotherapy 18, 19, 26, 27. In the current study, the first fever was observed within 8 weeks of initiation of therapy in all nine patients in whom pyrexia was observed, while the median time to onset of the first fever in a global clinical study conducted was reported to be 4.3 weeks after treatment initiation 27.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence indicates, however, that patients with brain metastases are nearly as likely to initi ally respond to BRAF-inhibitor therapy as those without brain metastases. In uncontrolled phase I-II trials of monotherapy with dabrafenib or vemurafenib in patients with melanoma brain metastasis [161][162][163] (TABLE 3), ORRs and PFS were only marginally inferior to those observed in trials that included only patients without active brain metastases. These benefits are presumed, although not yet proven, to translate into prolonged overall survival, and have led to BRAF-inhibitor therapy becoming a mainstay treatment for patients with untreated metastatic melanoma involving the brain.…”
Section: Response Criteriamentioning
confidence: 92%